P20 Pic study: prednisolone in children: prescribing, dispensing and administering prednisolone formulations to children with acute asthma or wheeze. Issue 2 (19th January 2018) - Venables, Rebecca; Haley, Helen; Gilchrist, Francis; Lenney, Warren
Abstract : Aim: To explore the current prescribing, dispensing and administration practice for oral prednisolone to children with acute asthma or wheeze. Method: A semi-structured telephone interview following a course of oral prednisolone. The interview questions were designed during consultation with a multidisciplinary team and explored: doses prescribed, formulations prescribed and dispensed, parent/legal guardian/patients' experiences and perceptions of prednisolone administration and medicines manipulation and adherence. Parents/legal guardians of children aged 2–11 years and young people over 12 years with acute asthma/wheeze prescribed a short course (≤7 days) of oral prednisolone on the Children's Assessment Unit (CAU) or in the out-patients department were eligible to consent/assent to this study. Ethical approval was granted. Results: 20 families completed the study. The ages of children ranged from 2–16 years (average=5 years). Specific formulation details (e.g. tablets, soluble tablets, EC tablets) were provided by prescribers in only 20% of the oral prednisolone prescriptions. There was variability in dispensing soluble versus tablet formulations across child ages; the average ages of children prescribed soluble tablets and non-soluble tablets were 4 years and 11 years respectively. 80% of oral prednisolone formulations dispensed were soluble tablets. In 40% of cases, manipulation techniques were provided by parents to improve patient acceptance of prednisolone soluble owing to its poor palatability. In addition, 2 parents discussed using coercion to improve acceptance. A high level of adherence to prednisolone was reported:95% of prednisolone courses were completed. All prescriptions were for duration of 2 or 3 days. Of the prednisolone doses recorded: 53% were in-line with trust guidance (0.5 mg/kg rounded up to the nearest 5 mg), 13% – BNFC guidance, 13% – BTS SIGN guidance and 20% (not in the guidance listed) were between 0.32 mg/kg and 0.76 mg/kg. Conclusion: There is no gold standard for prescribing, dispensing and administering prednisolone in young children, thus dosages and formulations prescribed vary widely. This study highlighted variability in dosing of prednisolone across different guidelines. There is very little information regarding the appropriateness of prescribing non-soluble versus soluble formulations for children, however tablet size should be considered when formulating medicines for children. 1 Soluble prednisolone tablets were dispensed more commonly than non-soluble in this hospital setting; however, the taste of prednisolone has been described as a barrier to medicines acceptance. 2 Although adherence in this cohort was high, the majority of children had received the formulation previously and palatability was described as an adherence issue during initial prescribing. Further information at the prescribing and dispensing stage is required to understand the factors influencing formulations and doses prescribed and dispensed. This research will inform larger studies investigating the suitability of formulations, advising: prescribers, Formulation teams and Healthcare Institutions on improving patient acceptability and medicines optimisation and increasing cost-benefit (e.g. through improving patient adherence and reducing medicines wastage and hospital admissions). Findings will support wider prescribing in other healthcare settings as the results will be easily translational across chronic conditions in all healthcare sectors. References: EMA. 2006. http://www.ema.europa.eu/docs/en_GB/document_library/Scientific_guideline/2009/09/WC500003782.pdf [Accessed: 03 July 2016]. Venables R, Marriott J, Stirling H. Find out: Key problems with children's medicines formulations … It's a taste issue! IJPP 2012;20(Supplement 2):23.